2020
DOI: 10.1063/1.5131516
|View full text |Cite
|
Sign up to set email alerts
|

In situ oxidation studies of Cu thin films: Growth kinetics and oxide phase evolution

Abstract: A comprehensive understanding of the oxidation of Cu thin films in the low-temperature regime is of fundamental interest and particularly relevant for applications in the fields of micro-and nanoelectronics, sensors, catalysis, and solar cells. The current study reports on the oxidation kinetics of PVD grown Cu thin films (20-150 nm thick) and the oxide phase evolution from Cu 2 O to CuO upon thermal oxidation in the temperature range of 100-450°C. XRD investigations in the laboratory and at the synchrotron sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 51 publications
2
43
4
Order By: Relevance
“…Low-temperature oxidation of Cu to Cu 2 O was reported to follow linear law [13,14] or logarithmic law [18]. Oxidation of Cu 2 O to CuO was reported to follow parabolic [13] or logarithmic [17] rate law.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-temperature oxidation of Cu to Cu 2 O was reported to follow linear law [13,14] or logarithmic law [18]. Oxidation of Cu 2 O to CuO was reported to follow parabolic [13] or logarithmic [17] rate law.…”
Section: Discussionmentioning
confidence: 99%
“…However, linear growth of the oxide layer has also been reported. Unutulmazsoy et al [13] studied the oxidation of Cu thin films in the temperature range of 100-450 • C and found that the formation of the CuO phase only starts after complete oxidation of Cu to Cu 2 O. The oxidation kinetics of Cu to Cu 2 O followed the linear rate law, which refers to surface reaction controlled oxidation, in the temperature range of 100-300 • C, whereas the oxidation kinetics of Cu 2 O to CuO seemed to be controlled by a parabolic rate law.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The as-deposited Cu thin films [face-centered cubic (f.c.c. ), Fm3m, a Cu = 3.615 Å ] have a pronounced {111} fiber texture (Unutulmazsoy et al, 2020). Accordingly, the 111, 200, 220 and 331 reflections were measured at specific tilt angles (depending on the texture).…”
Section: Xrd Characterizationmentioning
confidence: 99%
“…Studies in the literature show that the thickness of surface oxide layer in metallic films is 2-3 nm. [26,27] As the thickness of the top Hf layer is 4.3 nm, it follows that the 1-2 nm thick Hf layer interfaced with Fe would still be metallic. All the interface roughnesses are in the range of 0.3-0.5 nm.…”
mentioning
confidence: 99%